Parenting the Phoenix: Transformative learning experiences of parents of transgender and non-binary children - McNeilly, Elizabeth A. (The Canadian Journal for the Study of Adult Education / La revue canadienne pour l’étude de l’éducation des adultes)

(untitled) (Canadian Association for the Study of Adult Education / L’Association canadienne pour l’étude de l’éducation des adultes, 2023)
For many parents of transgender or non-binary children the experience is transformative learning (Mezirow, 1978). This life history study of 17 parents of children aged 6 to 29 comprised of 33 interviews, 10 participant journals, and an autoethnography. Findings from the data indicated parental learning was a holistic experience (Illeris, 2003), a balance of emotion, cognition, and sociality. When one domain of learning was overstimulated, learning could be disrupted. Parents restructured their conceptions of gender, working through understandings of gender from their past and new ideas of the present. Learning also occurred in two phases, a private phase of cognitive reframing and then a more public phase as parents learned to advocate for their child. Most parents were anchored by value of authenticity, and some mothers revisited the notion of “What makes a woman?” For some, working through discomfort was one part of the learning process.